HEMA Effects on Autophagy Mechanism in Human Dental Pulp Stem Cells - Francesca Diomede (Materials, 2019)
Autophagy is a complex mechanism that permits the degradation of cellular components in order to enhance cell homeostasis, recycling the damaged, dysfunctional, or unnecessary components. In restorative dentistry practice, free resin monomers of 2-hydroxyethyl methacrylate (HEMA) can be released. The aim of this study was to investigate the effect of HEMA on proliferation and autophagy in human dental pulp stem cells (hDPSCs). Human DPSCs were treated with different concentrations of HEMA (3 and 5 mmol L−1). To evaluate the proliferation rate, MTT and trypan blue assays were used. Autophagic markers such as microtubule-associated protein 1 light chain 3 (LC3-I/II) and ubiquitin-binding protein (p62) were analyzed through immunofluorescence observations. Beclin1, LC3-I/II, and p62 were evaluated by means of Western blotting detection. Considering that activity of extracellular signal−regulated kinase (ERK) and its phosphorylated form (pERK) mediates several cellular processes, such as apoptosis, autophagy, and senescence, the involvement of ERK/pERK signaling was also evaluated. Obtained results showed a decreased cell proliferation associated with morphological changes in HEMA-treated cells. The Western blot results showed that the expression levels of Beclin1, LC3-I/II, and ERK were significantly elevated in HEMA-treated cells and in cells co-treated with rapamycin, an autophagic promoter. The expression levels of p62 were significantly reduced compared to the untreated samples. Protein levels to the autophagic process, observed at confocal microscopy confirmed the data obtained from the Western blot. The up-regulation of ERK and pERK levels, associated with nuclear translocation, revealed that ERK pathway signaling could act as a promoter of autophagy in dental pulp stem cells treated with HEMA.